Correlation between fine and gross motor coordination in children - Amaro, Nuno (2016)
Physical activity is considered an excellent option to achieve an optimum health condition. However, college students are usually linked to a sedentary life style, compromising health and life quality. Previous studies stated that men are usually linked to exercise due to challenge and fitness, while women look for appearance and stress management.